Anandamide Alters Barrier Integrity of Bovine Vascular Endothelial Cells during Endotoxin Challenge - Carsten C. F. Walker; Lorraine M. Sordillo; G. Andres Contreras (MDPI AG, 2022)
Vascular endothelial cells are crucial mediators of inflammation during infectious diseases, due to their ability to produce lipid-based inflammatory mediators and facilitate leukocyte migration and translocation to infected tissues. Mastitis is the costliest infectious disease in North America, with over two billion dollars in annual costs due to loss of milk production, medical treatment, and potential loss of the animal. Infections caused by coliform bacteria are particularly deleterious, causing a negative impact on cow well-being and a high mortality rate. Dysfunction and breakdown of the endothelial barrier is a key part of the pathology of coliform mastitis. The endocannabinoid system (ECS), shown to modulate inflammatory responses of vascular endothelial cells in humans and rodents, may be a novel target for inflammatory modulation in dairy cows. The endocannabinoid (EC) arachidonoylethanolamide (AEA) is a potent anti- or pro-inflammatory mediator in endothelial cells, depending on location, timing, and concentration. We hypothesized that elevated AEA during LPS challenge will impair endothelial barrier integrity via increased production of reactive oxygen species (ROS) and activation of apoptotic pathways. Challenge of bovine aortic endothelial cells (BAEC) with 25 ng/mL lipopolysaccharide (LPS) for 8 h induced AEA synthesis, increased expression of cannabinoid receptor 1 and 2 (CB1/2) and the AEA synthesizing enzyme N-acyl phosphatidylethanolamine phospholipase D (NAPE-PLD), while decreasing gene expression of the AEA degradation enzyme fatty acid amide hydrolase (FAAH). Trans endothelial resistance (TER), measured through electrical resistance across the monolayer, increased 2 h after 0.5 µM AEA treatment and decreased with 5 µM AEA, compared to LPS alone. Addition of AEA to BAEC challenged with LPS induced mitochondrial dysfunction via increased ROS production, cytochrome-C release, and activation of caspase 3/7. Antagonism of CB1 by 1 µM AM251 ameliorated AEA induced ROS production and cytochrome-C release. Addition of AM251 also eliminated 2 h TER increase and improved TER following 5 µM AEA. Doses of 0.5, 1, and 5 µM AEA delayed endothelial barrier recovery, which was eliminated by the addition of AM251. Mitochondrial dysfunction and activation of apoptotic pathways in response to AEA treatment during LPS challenge of BAEC may act to delay inflammatory resolution and contribute to endothelial dysfunction.